Role of serotonin in plant stress responses: Quo vadis? - Sun, Like; Yin, Jiaxi; Wang, Long; Li, Jingjing; Hu, Can; Liu, Bo; Zheng, Chenfan; Chen, Jiale; Fotopoulos, Vasileios; Shu, Qingyao; Jiang, Meng (My University, 2025)
Serotonin (5-hydroxytryptamine (5-HT)) is a pineal hormone and a secondary metabolite related to various hormonal and physiological functions at the organ, tissue, and cellular levels. It is considered increasingly important in regulating animal behavior, but the function of serotonin in plants is far less known. According to recent research, serotonin is vital for plant growth, development, and stress responses, achieved through transcriptional and phytohormonal interplay. Specifically, this review addresses critical gaps in the understanding of serotonin's function in plants by examining its biosynthesis, metabolism, and its multifaceted role in mitigating both abiotic stresses (salinity, drought, heat, cold, and heavy metals) as well as biotic challenges (pathogens, pests, and herbivores). As a pivotal player, it engages in a variety of significant cellular and molecular interactions, including those with reactive oxygen and nitrogen species (RONS), and various phytohormones such as auxin, abscisic acid (ABA), salicylic acid (SA), jasmonic acid (JA), ethylene (ET), and cytokinin (CK). Advances in serotonin-related research are anticipated to offer a valuable basis for uncovering the regulatory pathways by which serotonin impacts the resilience of crops against abiotic stress.
Keywords: abiotic and biotic stress; biosynthesis; metabolism; phytohormone; reactive oxygen and nitrogen species; serotonin